(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease predominantly affecting women during reproductive age. Gynecological manifestations associated with SLE significantly influence menstrual health, fertility, cervical pathology, and sexual well-being. However, available evidence regarding the prevalence and spectrum of gynecological complications in women with SLE remains inconsistent. Objective: To systematically evaluate gynecological manifestations associated with systemic lupus erythematosus and estimate the pooled prevalence of reproductive and gynecological complications among women with SLE. Methods: A systematic review and meta-analysis was conducted according to PRISMA guidelines. Electronic databases including PubMed, Scopus, Embase, Web of Science, and Google Scholar were searched for observational studies published between January 2000 and January 2025. Studies assessing gynecological manifestations among women diagnosed with SLE were included. Random-effects meta-analysis was performed to estimate pooled prevalence and pooled odds ratios (ORs) with 95% confidence intervals (CI). Results: A total of 42 studies involving 18,764 women with SLE were included. Menstrual irregularities represented the most common gynecological manifestation with a pooled prevalence of 38.6% (95% CI: 33.1–44.2). Premature ovarian insufficiency was observed in 16.9% (95% CI: 12.4–21.8), while infertility-related complications were reported in 21.4% (95% CI: 17.2–25.9). Women with SLE demonstrated significantly higher odds of cervical dysplasia (OR 2.12, 95% CI: 1.54–2.91) and human papillomavirus infection (OR 2.37, 95% CI: 1.69–3.31). Cyclophosphamide exposure, prolonged disease duration, and high disease activity were major risk factors associated with gynecological complications. Conclusion: Gynecological manifestations are highly prevalent among women with systemic lupus erythematosus and significantly affect reproductive and sexual health outcomes. Early screening, fertility preservation strategies, multidisciplinary care, and regular gynecological assessment are essential components of comprehensive SLE management.